Nonlinear behaviors analysis of high-speed rotor system supported by aerostatic bearings. (June 2022) - Zhang, Jianbo; Han, Dongjiang; Xie, Zhongliang; Huang, Chao; Rao, Zhushi; Song, Mingbo; Su, Zhimin
Abstract: In the paper, the dynamic model of aerostatic bearing-rotor system combining rotor motion equation and transient Reynolds equation is established to study influences of rotational speed, unbalance, rotor mass and supply pressure on the nonlinear behaviors of rotor system. The results reveal abundant nonlinear phenomenon consisting of 3 T-periodic, 5 T-periodic and quasi-periodic motions. Furthermore, chosen proper unbalance, smaller rotor mass and larger supple pressure can control the nonlinear vibration and improve the system stability. The results provide a theoretical basis for a simple and feasible method to control the nonlinear vibration of rotor system by adjusting supply pressure. Highlights: The dynamic model of aerostatic bearing-rotor system combining transient Reynolds equation and FEM rotor dynamic equation is established to study the effects of rotational speed, supply pressure, unbalance and rotor mass on the nonlinear behaviors of rotor system theoretically. The numerical simulation results reveal complex nonlinear behaviors comprising 3 T-periodic, 5 T- periodic and quasi-periodic motion under high rotational speed condition. Chosen proper unbalance, smaller rotor mass and larger supple pressure can control the nonlinear vibration and improve the stability of system. The rotational speed of generating the nonlinear vibration can be enhanced by increasing supply pressure. The simulation results can provide a theoretical basis that adjustment of supply pressure is a simple and feasible method of control nonlinear vibration in operation process of the rotor system.